Diffracted X-ray blinking reveals signature crystal polymorph dynamics in 1,2,3,5-Tetrabromobenzene - Keegan McGehee; Koichiro Saito; Ryo Fukaya; Rie Haruki; Shunsuke Nozawa; Minghao Gao; Yuji C. Sasaki; Kazuhiro Mio; Yasuo Norikane (Scientific Reports)
Abstract In this work we report findings on the study of 1,2,4,5-tetrabromobenzene (TBB) polymorphs by diffracted X-ray blinking (DXB). Using DXB it was found that on the ms-s time scale subtle fluctuations in the d-spacing between lattice planes occurs more rapidly in the γ-phase polymorph than in the β-phase, successfully identifying another distinct characterization between them. It was also found that the rate of molecular motion spiked near the phase transition temperature beyond the typical characteristic regions. This offers additional insight on previous reports of anisotropic lattice softening and strain accumulation near the phase transition temperature that are key to the mechanically responsive properties of TBB crystals. The present study on ms-s crystalline dynamics by DXB for mechanically responsive organic crystals also serves as a guideline for future study of more complicated mechanically responsive crystal behaviors.